2010
DOI: 10.1590/s0102-695x2010005000047
|View full text |Cite
|
Sign up to set email alerts
|

Chemical constituents from Astragalus annularis Forssk. and A. trimestris L., Fabaceae

Abstract: The phytochemical investigation of the aerial parts of Astragalus annularisForssk. and A. trimestris L., Fabaceae, growing in Egypt, resulted in the isolation of eight compounds, for the first time from these two species. These compounds were identified by chemical methods, NMR spectroscopy, UV spectroscopy as well as MS analysis. The antimicrobial activity of the isolated compounds were tested against Staphylococcus aureus, Esherichia coli and Candida albicans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 21 publications
1
18
0
Order By: Relevance
“…31 Its presence was previously confirmed in two other genus of Rosaceae family -Amygdalus and Prunus. 34 Having this in mind significant biological activity of the extract exhibited in this investigation can be potentially ascribed to combined or synergistic effects. 23 The antimicrobial activity of compounds presented in the studied extract is also previously investigated.…”
Section: Chemical Analysismentioning
confidence: 90%
“…31 Its presence was previously confirmed in two other genus of Rosaceae family -Amygdalus and Prunus. 34 Having this in mind significant biological activity of the extract exhibited in this investigation can be potentially ascribed to combined or synergistic effects. 23 The antimicrobial activity of compounds presented in the studied extract is also previously investigated.…”
Section: Chemical Analysismentioning
confidence: 90%
“…24 Soyasaponin I (9) was previously isolated from many Astragalus species. 7,19,25 However, this is only the second report of the occurrence of dehydrosoyasaponin I (10) in this genus. 7 According to the literature data, this is also the first occurrence of the compounds 2-8 in the genus Astragalus.…”
Section: Resultsmentioning
confidence: 80%
“…In this study, 13 known compounds were isolated, including seven flavonoids, identified as kaempferol 3-O-rutinoside (nicotiflorin, 1), 12 15 3′,5′-di-C-β-D-glucopyranosylphloretin (6) and hovetrichoside C (8), 16,17 one lignan, i.e., isolariciresinol 9′-O-β-D-glucopyranoside (7), 18 two saponins, i.e., soyasaponin I (9) and dehydrosoyasaponin I (10), 19,20 two sterols, i.e., β-sitosterol (11) and β-sitosterol 3-O-glucoside (12), 21 and one triterpenoid, i.e., lupeol (13). 22 Their structures were elucidated by extensive spectroscopic methods including 1D ( 1 H and 13 C) and 2D NMR (COSY, HSQC and HMBC) experiments as well as ESI-MS analysis (see Supplementary material) and by comparison with those reported in literature (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The phytochemical study of ASH-2a fraction led us to obtain the triterpene squalene (1), which was identified by comparison of its fragmentation pattern with those in the NIST library provided by the GC-MS. Study of ASH-2c fraction allowed the isolation of the flavone sorbifolin (4) and two glycosylated flavones: cirsimarin (3) and sorbifolin-6-O-ˇ-glucopyranoside (5), which were identified by comparison of their spectroscopic data with those reported in the literature (Fernandes et al, 2008;Lin et al, 2006;Yim et al, 2003). Sorbifolin has been isolated from the species Astragalus annularis (El-Hawiet et al, 2010) and Pterogyne nitens from Fabaceae family (Fernandes et al, 2008); Heterotheca subaxilaris (Morimoto et al, 2009) and Pulicaria uliginosa (Eshbakova et al, 1996) from Asteraceae; and R. tuberosa from Acanthaceae (Lin et al, 2006). Regarding its biological activities, this flavonoid has been tested in antimicrobial, antioxidant, and myeloperoxidase bioassays, resulting in moderate to null activity (El-Hawiet et al, 2010;Fernandes et al, 2008).…”
Section: Resultsmentioning
confidence: 99%
“…Sorbifolin has been isolated from the species Astragalus annularis (El-Hawiet et al, 2010) and Pterogyne nitens from Fabaceae family (Fernandes et al, 2008); Heterotheca subaxilaris (Morimoto et al, 2009) and Pulicaria uliginosa (Eshbakova et al, 1996) from Asteraceae; and R. tuberosa from Acanthaceae (Lin et al, 2006). Regarding its biological activities, this flavonoid has been tested in antimicrobial, antioxidant, and myeloperoxidase bioassays, resulting in moderate to null activity (El-Hawiet et al, 2010;Fernandes et al, 2008). Meanwhile, isolation of cirsimarin has been reported from species such as R. tuberosa, Cirsium lineare, C. rhinoceros, Teucrium arduini and M. debilis (Vukovic et al, 2011;Bai et al, 2011;Jeong et al, 2008;Lin et al, 2006;Yim et al, 2003).…”
Section: Resultsmentioning
confidence: 99%